A DISCOURSE ANALYSIS OF MEDICINE ADVERTISEMENTS IN ENGLISH AND VIETNAMESE - Ph.D NGUYỄN THỊ QUỲNH HOA (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The language of advertising is a very special one which has its own characteristics that make it different from other languages. This study aims at conducting a discourse analysis of medicine advertisements in English and Vietnamese. The descriptive and contrastive methods are employed to give a detailed description of some typical discourse features and to point out the similarities and differences between English medicine advertisements (EMAs) and Vietnamese medicine advertisements (VMAs) in terms of their layout, lexical choices, syntactic structures and cohesive devices. In addition, the findings of this study are clearly presented based on a survey of 60 medicine advertisements in English and another 60 ones in Vietnamese which are taken from well-known medical magazines. It is hoped that the results of this study will really provide some practical applications for teaching and learning English for students who major in Pharmacist Assistants Training.